The effects of maternal position, in late gestation pregnancy, on placental blood flow and oxygenation: an MRI study. (18th January 2021) - Couper, Sophie; Clark, Alys; Thompson, John M. D.; Flouri, Dimitra; Aughwane, Rosalind; David, Anna L.; Melbourne, Andrew; Mirjalili, Ali; Stone, Peter R.
Abstract : Key points: Maternal supine sleep position in late pregnancy is associated with an increased risk of stillbirth. Maternal supine position in late pregnancy reduces maternal cardiac output and uterine blood flow. Using MRI, this study shows that compared to the left lateral position, maternal supine position in late pregnancy is associated with reduced utero‐placental blood flow and oxygen transfer across the placenta with an average 6.2% reduction in oxygen delivery to the fetus and an average 11% reduction in fetal umbilical venous blood flow. Abstract: Maternal sleep position in late gestation is associated with an increased risk of stillbirth, though the pathophysiological reasons for this are unclear. Studies using magnetic resonance imaging (MRI) have shown that compared with lateral positions, lying supine causes a reduction in cardiac output, reduced abdominal aortic blood flow and reduced vena caval flow which is only partially compensated for by increased flow in the azygos venous system. Using functional MRI techniques, including an acquisition termed diffusion–relaxation combined imaging of the placenta (DECIDE), which combines diffusion weighted imaging and T2 relaxometry, blood flow and oxygen transfer were estimated in the maternal, fetal and placental compartments when subjects were scanned both supine and in left lateral positions. In late gestation pregnancy, lying supine caused a 23.7% ( P < 0.0001) reduction in total internal iliac arterial blood flow to the uterus. In addition, lying in the supine position caused a 6.2% ( P = 0.038) reduction in oxygen movement across the placenta. The reductions in oxygen transfer to the fetus, termed delivery flux, of 11.2% ( P = 0.0597) and in fetal oxygen saturation of 4.4% ( P = 0.0793) did not reach statistical significance. It is concluded that even in healthy late gestation pregnancy, maternal position significantly affects oxygen transfer across the placenta and may in part provide an explanation for late stillbirth in vulnerable fetuses. Key points: Maternal supine sleep position in late pregnancy is associated with an increased risk of stillbirth. Maternal supine position in late pregnancy reduces maternal cardiac output and uterine blood flow. Using MRI, this study shows that compared to the left lateral position, maternal supine position in late pregnancy is associated with reduced utero‐placental blood flow and oxygen transfer across the placenta with an average 6.2% reduction in oxygen delivery to the fetus and an average 11% reduction in fetal umbilical venous blood flow.